Iron and Ferritin Modulate MHC Class I Expression and NK Cell Recognition - Sottile, Rosa; Federico, Giorgia; Garofalo, Cinzia; Tallerico, Rossana; Faniello, Maria Concetta; Quaresima, Barbara; Cristiani, Costanza Maria; Di Sanzo, Maddalena; Cuda, Gianni; Ventura, Valeria; Wagner, Arnika Kathleen; Contrò, Gianluca; et al. (Frontiers in Immunology, 2019)
The ability of pathogens to sequester iron from their host cells and proteins affects their virulence. Moreover, iron is required for various innate host defense mechanisms as well as for acquired immune responses. Therefore, intracellular iron concentration may influence the interplay between pathogens and immune system. Here, we investigated whether changes in iron concentrations and intracellular ferritin heavy chain (FTH) abundance may modulate the expression of Major Histocompatibility Complex molecules (MHC) and susceptibility to Natural Killer (NK) cell cytotoxicity. FTH downregulation, either by shRNA transfection or iron chelation, led to MHC surface reduction in primary cancer cells and macrophages. On the contrary, mouse embryonic fibroblasts (MEFs) from NCOA4 null mice accumulated FTH for ferritinophagy impairment and displayed MHC class I cell surface overexpression. Low iron concentration, but not FTH, interfered with IFN-γ receptor signaling, preventing the increase of MHC-class I molecules on the membrane by obstructing STAT1 phosphorylation and nuclear translocation. Finally, iron depletion and FTH downregulation increased the target susceptibility of both primary cancer cells and macrophages to NK cell recognition. In conclusion, the reduction of iron and FTH may influence the expression of MHC class I molecules leading to NK cells activation. Keywords: MHC-I, NK cells, iron